(untitled) (Journal of Medicine, 2012)
Guillain-Barre syndrome is a post infectious ascending, usually demyelinationg polyradiculoneuropathy. Dengue fever as an antecedent infection in GBS is uncommon. A 39-year-old female presented with acute flaccid weakness of both upper and lower limbs which developed in ascending and progressive fashion following a febrile illness of three days. During work-up IgM for dengue virus was found positive. Diagnosis of Guillain-Barre syndrome was made based on neurologic manifestations, the typical CSF findings and pattern of electrophysiological study and exclusion of other pathologies. Patient was treated with intravenous immunoglobulins. During the course of illness, she developed lower motor neuron type trigeminal, facial, glossopharyngeal, vagus and hypoglossal nerve palsy and autonomic involvement. She had significant recovery and was able to talk, eat and walk six weeks later. Dengue is endemic in Bangladesh. Post dengue Guillain- Barre syndrome in adult, as shown in previous reports, should now be considered in the part of spectrum of neurological complications of this infection. DOI: http://dx.doi.org/10.3329/jom.v13i2.12772 J Medicine 2012; 13 : 246-249